ANALISIS KOMPETENSI PENDAMPING PROGRAM KELUARGA HARAPAN DALAM MENINGKATKAN KINERJA KOTA MAKASSAR - Arnika, Mita; Adys, Abdul Kadir; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2022)
This research tries to describe the theory of competence to see the performance of family program companion hope. Competence is needed to improve co-performance in Makassar city. Competence becomes one of the important factors to improve performance. This method uses qualitative methods with the type of deskriptif. The result of the research shows that there is an influence of competence of the accompanist of family program of hope to improve the performance of PKH assistant in Makassar city. It is viewed from two demension namely 1) Demand of intention in the form of personal character motivation, control of knowledge, 2) Dimension of action in the form of skill. it shows that greatly affect the performance performance of companion Program family hope with existence of competence possessed well can improve good performance.